Measuring the importance of health domains in psoriasis: discrete choice experiment versus rating scales - Gutknecht, Mandy; Schaarschmidt, Marthe-Lisa (Patient preference and adherence, 2018)
Measuring the importance of health domains in psoriasis – discrete choice experiment versus rating scales Mandy Gutknecht,1 Marthe-Lisa Schaarschmidt,1,2 Marion Danner,3 Christine Blome,1 Matthias Augustin1 1German Center for Health Services Research in Dermatology (CVderm), Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Hamburg, Germany; 2Department of Dermatology, University Medical Center Mannheim, Heidelberg University, Mannheim, Germany; 3Institute for Health Economics and Clinical Epidemiology (IGKE), University Hospital of Cologne, Cologne, Germany Background: Psoriasis affects different aspects of health-related quality of life (eg, physical, psychological, and social impairments); these health domains can be of different importance for patients. The importance of domains can be measured with the Patient Benefit Index (PBI). This questionnaire weights the achievement of treatment goals by Likert scales (0, “not important at all” to 4, “very important”) using the Patient Needs Questionnaire (PNQ). Treatment goals assessed with the PBI have been assigned to five health domains; the importance of each domain can be calculated as the average importance of the respective treatment goals. In this study, the PBI approach of deriving importance weights is contrasted to a discrete choice experiment (DCE), in order to determine the importance of health domains in psoriasis, and to find if the resulting weights will differ when derived from these two methods.Methods: Adult patients with psoriasis completed both questionnaires (PNQ, DCE). The PBI domains were used as attributes in the DCE with the levels “did not help at all”, “helped moderately”, and “helped a lot”.Results: Using DCE, “improving physical functioning” was the most important health domain, followed by “improving psychological well-being”. Using PNQ, these domains were ranked in position two and three following “strengthening confidence in the therapy and in a possible healing”. The latter was least important using DCE. The only agreement of ranking was shown in “reducing impairments due to therapy” (position four). “Improving social functioning” was ranked in position three (DCE) and five (PNQ).Conclusion: Health domains have different importance to patients with psoriasis. Using PNQ or DCE to determine the importance of domains results in markedly different rankings; both approaches can thus not be considered equivalent. However, in this study, importance was assessed at the domain level in DCE and at the single item level in PNQ, which may have added to the differences.